A violent minority? A quantitative analysis of those engaged in anti-immigrant violence in South Africa. Issue 2 (4th May 2019) - Gordon, Steven
ABSTRACT: Xenophobic violence poses a clear threat to South Africa, especially in light of the country's treaty commitments to 'open borders' following the 30 th Ordinary Assembly of the African Union. Civil society organizations have been highly critical of government efforts to prevent xenophobic violence in the country. The aim of this study is to profile the determinants of individual participation in anti-immigrant violence. The article focused on both past and potential participation in this type of behaviour. My central thesis is that there is a robust correlation between involvement in peaceful organized anti-immigrant activities (e.g. boycotts and demonstrations) and participation in xenophobic violence. For this study, data from the 2015–2017 rounds of the South African Social Attitudes Survey ( N  = 9, 292) was utilized. Bivariate and multivariate techniques were used to show that past and potential involvement in violent behaviour was strongly correlated with previous experience with peaceful anti-immigrant activity. By moving beyond a narrow focus on fixed episodes of collective violence, this article demonstrates the importance of a geographical analysis of xenophobic behaviour. However, there are limitations to the dataset used for this study and the article concludes by outlining future areas of research.